The Road to Recovery: Building Physical and Emotional Trust when Engaging with Extension Clientele - Colby Jordan Silvert; Cody Gusto; John Diaz (EDIS, 2020)
Now is a crucial time for Extension professionals to engage with clientele. In both urban and rural communities, clients are facing a multitude of unprecedented challenges related to COVID-19. Many Extension professionals already have experience in emergency and disaster preparedness, response, and recovery that can be applied in the present context. However, we must rethink how we interact with and assist clientele to ensure their safety and our own. To do this, it is critical we understand that the pandemic has exacerbated emotional trauma and anxiety resulting in trust gaps. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication aims to build Extension professionals’ sensitivity to the needs and emotional strains that COVID-19 presents for clients, and the strategies needed for effective recovery. Written by Colby Silvert, Cody Gusto, and John Diaz. https://edis.ifas.ufl.edu/wc376